2019
DOI: 10.1148/radiol.2018180867
|View full text |Cite
|
Sign up to set email alerts
|

A Decision Analysis of Follow-up and Treatment Algorithms for Nonsolid Pulmonary Nodules

Abstract: onsolid nodules (sometimes known as subsolid nodules), which include ground-glass nodules (GGNs) and part-solid nodules (PSNs), are commonly identified on chest CT images. These are found in approximately 9% of patients undergoing low-dose CT for lung cancer screening (1,2). Although some nonsolid nodules are transient and likely inflammatory (1,2), many of those that persist range from premalignant lesions to invasive adenocarcinomas (3,4). Nonsolid nodules are more likely to represent lung cancer than solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Simulation modeling has suggested superior outcomes with stereotactic body radiation therapy compared with lobectomy or nontherapy for SSNs. 80 However, trials comparing these treatments to establish noninferiority of ablative options have failed to accrue participants. The gold standard remains surgical resection for patients who are surgical candidates.…”
Section: Tissue Sampling and Treatment Optionsmentioning
confidence: 99%
“…Simulation modeling has suggested superior outcomes with stereotactic body radiation therapy compared with lobectomy or nontherapy for SSNs. 80 However, trials comparing these treatments to establish noninferiority of ablative options have failed to accrue participants. The gold standard remains surgical resection for patients who are surgical candidates.…”
Section: Tissue Sampling and Treatment Optionsmentioning
confidence: 99%
“…Given the indolent behavior and low metastatic potential for subsolid adenocarcinomas, the benefits of surgery are likely reduced in these cancers. One simulation-based analysis suggested that radiation therapy may even provide improved outcomes in these patients because of less treatment-related morbidity and mortality [ 35 ]. Future research is needed in this arena to better define the benefits of surgery versus non-surgical management of subsolid malignancies.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…By simulating a sufficiently large number of patients (N ¼ 10,000,000), we ensured that the results would be stable. Some elements of the model's structure are described here; others are detailed in Supplementary Section 1 and the supplement of Hammer et al 12 We used results from the literature and from secondary data analysis of the NLST data 13 to estimate model parameters, including nodule size, growth rate distributions, and patient characteristics, such as age and smoking status. In addition to modeling malignancy developing from subsolid nodules, we allowed for the development of incidental lung cancers.…”
Section: Model Overviewmentioning
confidence: 99%
“…For this analysis, patient-level age-and smoking status-dependent incidental cancer rates were derived using the PLCOm2012 model, 14 with the Smoking History Generator 15,16 used to model individuals' smoking history. The probability of patient death at any given month depends on age, smoking status, presence and stage of clinically significant lung cancer, and whether the patient had received treatment, as detailed in the Supplement, Section 1 and Hammer et al 12…”
Section: Model Overviewmentioning
confidence: 99%
See 1 more Smart Citation